Evaluation and Specifications for In-Line Uranium Separations Using Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES) Detection for Trace Elemental Analysis. Issue 8 (August 2019) - Manard, Benjamin T.; Metzger, Shalina C.; Quarles, C. Derrick; Rogers, Kayron T.; Ticknor, Brian W.; Bostick, Debra A.; McBay, Eddy H.; Hexel, Cole R.
Automated introduction platforms integrated with inductively coupled plasma optical emission spectroscopy (ICP-OES) systems are continuously being improved. Expanding on the introduction systems, a newly developed automated ion chromatography system was explored for performing rapid in-line separations coupled to ICP-OES for the detection of trace elements in uranium. Trace elements are separated from a uranium material and the analytes are directed into the ICP-OES for subsequent detection. Detection parameters such as exposure time frequency, wavelength selection, and settling times were explored to gain insight on optimal detection schemes for in-line trace elemental analysis. The methodology was applied in the analysis of a uranium oxide (U3 O8 ) certified reference material, CRM-124. It was found here that the sensitivity and uncertainty of the technique are greatly affected by how the ICP-OES is employed to collect data. Overall it was determined that faster exposure replicates can provide greater peak resolution with higher fidelity measurements but are limited with respect to the total analysis time (i.e., limited in detection timely separations). Zeta scores, which combine accuracy and uncertainty of certified values and experimental values, were used to validate the ICP-OES modes of operation.